2011
DOI: 10.1103/physreva.84.023815
|View full text |Cite
|
Sign up to set email alerts
|

General scaling limitations of ground-plane and isolated-object cloaks

Abstract: We prove that, for arbitrary three-dimensional transformation-based invisibility cloaking of an object above a ground plane or of isolated objects, there are practical constraints that increase with the object size. In particular, we show that the cloak thickness must scale proportional to the thickness of the object being cloaked, assuming bounded refractive indices, and that absorption discrepancies and other imperfections must scale inversely with the object thickness. For isolated objects, we also show tha… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 59 publications
1
22
1
Order By: Relevance
“…The only assumptions are that the ambient medium ε a and µ a is approximately lossless and dispersionless over the bandwidth of interest (e.g. for cloaking in air) and that the attainable refractive index contrast (eigenvalues of εµ/ε a µ a ) is ≤ B for some finite bound B (similar to our previous work [3]). Our analysis in the following subsections constitutes the following steps.…”
Section: Derivationmentioning
confidence: 99%
See 4 more Smart Citations
“…The only assumptions are that the ambient medium ε a and µ a is approximately lossless and dispersionless over the bandwidth of interest (e.g. for cloaking in air) and that the attainable refractive index contrast (eigenvalues of εµ/ε a µ a ) is ≤ B for some finite bound B (similar to our previous work [3]). Our analysis in the following subsections constitutes the following steps.…”
Section: Derivationmentioning
confidence: 99%
“…If the ambient materials are ε a and µ a , then an ideal cloak is obtained by constructing the materials ε = J ε a J ′ / det J and µ = J µ a J ′ / det J in the cloak, where J is the Jacobian matrix of the transformation. In our previous work [3] we showed that the cloaking problem at one frequency becomes increasingly difficult as the size of the object being cloaked increases. In particular, we proved that the imperfections due to absorption losses and random fabrication disorder must decrease asymptotically with the object diameter in order to maintain "good" cloaking performance: for the total (scattering + absorption) cross-section to be less than a given fraction f of a geometric cross section s g .…”
Section: Derivationmentioning
confidence: 99%
See 3 more Smart Citations